POTENTIAL ATTRACTIVENESS OF SINGKAWANG CAP GO MEH FESTIVAL - Ika Suryono Djunaid; Febriana Lisanti (Jurnal Cakrawala Ilmiah, 2022)
The Cap Go Meh Festival is an ethnic Chinese tradition derived from the words Cap Go meaning fifteen and Meh meaning night, so Cap Go Meh is the fifteenth night. Cap Go Meh is celebrated every year on the fifteenth day after the Chinese New Year, this is an annual event in Singkawang City. This festival is also called the here ditary celebration which is always commemorated by the Chinese tribe. and support by the local governmentasone of the biggest annual events.The Cap Go Meh celebration in Singkawang City is a unique tradition because it is a localculture with Chinese ethnicity. The Cap Go Meh tradition in Singkawang City has become one of the attractions for local and foreign tourists. Usually there is a show that is always displayed in the celebration of Cap Go Meh Singkawang. This study aims to find out (1) Attractions found at the Cap Go Meh Festival in Singkawang City (2) Amenity found at the Cap Go Meh in Singkawang City (3) Accessibility founf at the Cap Go Meh in Singkawang City (4) Ancilliary found at the Festival in Singkawang City. collection techniquesuse dare observation,study documentation andin- depthin terviews. The data analysis techniquerefersto the concept of (Huberman, 1992). There sults of the study show that the Cap Go Meh Festival has a unique and high cultural preservation. Improvement efforts can be made both internally from people and event sand the event attracts the attention of visitors to participate.Suggestions that can be submitted on the results of this study are addressed to the organizers, the people of Singkawang City and the local government by paying attention to cultural preservation